Treaty Between the United States of America and the French Republic, Art. III, Apr. 30, 1803, 8 Stat. 202, T. S. No. 86 - (:unkn) unknown (General Publisher, 1803)
Granted the inhabitants of the ceded territory all rights, advantages, and immunities of a full US citizen.
--
Keywords: GUARANTEED RIGHT